The Principle of Prioritizing the Recommended over the Obligatory When Its Benefit is Greater Exemplified by Imam Al-Qarafi (May Allah Have Mercy on Him) - Nada Khamis Hassan Jassim (Islamic Sciences Journal, 2025)
Due to the importance of the subject, I chose to examine a specific aspect of the science of Usul al-Fiqh (Principles of Islamic Jurisprudence) as discussed by Imam Al-Qarafi (may Allah have mercy on him). This aspect pertains to prioritizing the recommended (Mandoob) over the obligatory (Wajib) when the benefit of the recommended action is greater and more complete in terms of the magnitude of reward. This study explores the scenarios mentioned by Imam Al-Qarafi in his works, which involve giving precedence to the recommended over the obligatory based on the greater reward and benefit. After researching the topic, I formulated a title for this principle: "The Principle of Prioritizing the Recommended over the Obligatory When Its Benefit Is Greater." Additionally, I highlighted scholars who preceded Imam Al-Qarafi in addressing this issue, particularly when it relates to the magnitude of reward and the completeness of benefit.